CSR PRACTICES: AN ANALYSIS OF THE IMPACT OF SOCIETAL AND ENVIRONMENTAL COMMITMENT ON THE PERFORMANCE OF SMES IN THE CAMEROONIAN CONTEXT - Mballa Atangana, Yves; Barouwa, Yayé; Lewe Nguepnang, Armel (International Journal of Research -GRANTHAALAYAH, 2023)
This article explores the deliberate and/or imposed incorporation of CSR practices by SMEs in the African context, focusing on the influence of these practices on the quest for performance by Cameroonian SMEs. The deployment of CSR practices is part of the utilitarian "social issue management" trend in an approach based on societal and environmental analysis. Based on the specificity of the African environment and on the theoretical division, the coexistence of the formal and informal sector with the predominance of the informal over the formal, our results reveal in priority a societal and environmental commitment in CSR practices, a guarantee of performance in terms of environmental protection, endowment of a social charter and increase of new market shares. The reputation of the SME is reinforced in its ecosystem, allowing it to transform itself and legitimise itself with the various stakeholders.